Social Support and the Incidence of Cognitive Impairment Among Older Adults in China: Findings From the Chinese Longitudinal Healthy Longevity Survey Study - Yin, Shufei; Yang, Quan; Xiong, Jinli; Li, Tian; Zhu, Xinyi (Frontiers in Psychiatry, 2020)
Objective: Social support shows a protective effect against cognitive impairment in older adults. However, the longitudinal relationship between the distinct sources of social support and incidence of cognitive impairment remains unclear. This study aims to investigate the association between different sources of social support and the incidence of cognitive impairment among older adults in China. Method: We used longitudinal data (2005-2014) from the Chinese Longitudinal Healthy Longevity Survey (CLHLS, 2005-2014, mean follow-up years 5.32 ± 2.64). In total, 5897 participants (aged 81.7 ± 9.7 years, range 65-112 years, 49.0% male) were enrolled. Cognitive impairment was measured by the Mini-Mental State Examination (MMSE). Social support included support from family (marital status; contact with children, siblings, relatives, friends and others; money received from children; children’s visit; siblings’ visit) and the availability of support from social community (social service, social insurance). We calculated subdistribution hazard ratios (SHR) of cognitive impairment by establishing Cox regression models, adjusting for residence, gender, age, education, participation in physical exercise, activities of daily living, smoking, drinking, negative well-being, baseline cognitive function, occupation, leisure activities, and diseases. Results: Children’s visit and marital status were significantly associated with a lower incidence rate of cognitive impairment. However, social support from other resources did not consistently predict the incidence of cognitive impairment. Specifically, (1) participants who were married had a lower incidence rate of cognitive impairment compared to those who were widowed (SHR = 0.840, 95% confidence interval, 0.722-0.976, p = 0.023); (2) participants who were frequently visited by their children had a lower incidence of cognitive impairment compared to those who were not (SHR = 0.798, 95% confidence interval, 0.664-0.960, p = 0.017). Conclusion: Social support from family predicts a lower incidence of cognitive impairment among Chinese older adults.